Biologics-induced immunophenotypic cross-switching in patients with psoriasis and atopic dermatitis - Yanyan Li; Hong Liu; Furen Zhang (Wolters Kluwer Medknow Publications, 2023)
Antibody-based therapies that inhibit pro-inflammatory cytokine signalling are commonly used in dermatology. Paradoxically, these biological agents may induce or exacerbate paradoxical reactions. Recently, it has been reported that the treatment of eczema with dupilumab can lead to the development of psoriasiform eruptions, which we called psoriasiform paradoxical reactions (P-PRs). Conversely, cases of eczematous paradoxical reactions (E-PRs) have also been described in patients with psoriasis treated with biologics. To summarise the case characteristics and disease features of phenotypic transition between psoriasis and eczematoid dermatitis, and to explore the mechanism or connection related to biological agents or patients' genetic characteristics, a systematic review was conducted for P-PRs in atopic dermatitis and E-PRs in patients with psoriasis treated with corresponding biological agents, respectively. We identified a series of P-PRs in 42 atopic dermatitis cases treated with dupilumab. The time to onset of P-PRs typically ranged from weeks to months, with a mean latency period of 22.65 weeks. Almost all patients presented with new-onset P-PRs. Simultaneously, we reviewed 22 articles reporting 51 patients with psoriasis with biological agent-induced E-PRs, which occurred on average at 24.47 weeks, 72.55% of them induced by IL-17A inhibitors. 48.98% (24/49) of cases reported a positive personal history of atopy, which may suggest an increased risk of biological agent-induced paradoxical eruptions. Overall, the improvement or resolution upon discontinuation of the inciting biologics was relatively common, and further studies are needed to estimate the real prevalence and unveil the pathophysiological mechanisms of these paradoxical events.